Pengaruh BOPO, ROA, dan LDR Terhadap Agresivitas Pajak pada Perusahaan Sub Sektor Perbankan yang terdaftar di BEI Sebelum dan Saat Covid-19 - Kusuma Dewi; Damayanti Damayanti; Eksa Ridwansyah (Jurnal Ilmiah ESAI, 2023)
This study aimed to examine the effect of Operating Expenses on Operating Income (BOPO), Return On Assets (ROA), and Loan To Deposit Ratio (LDR) on tax aggressiveness in banking sub-sector companies listed on the IDX before and during Covid-19. The sample selection using the purposive sampling method was obtained as many as 25 with the 2018-2021 observation period (before and during Covid-19). The analysis technique used in this research is multiple linear regression analysis. The analysis uses SPSS version 22. The results of this study indicate that BOPO has an effect on tax aggressiveness, and ROA and LDR have no effect on tax aggressiveness.